The development of a Discharge Planning Model for pediatric patients with asthma at Sunpasitthiprasong Hospital - Thiwong, Porntipa; Cheevakasemsook, Aree; Pinyopasakul, Wanpen (Thai Journal of Nursing, 2020)
The purposes of this research and development were 1) to study problem situations and develop a discharge planning model for pediatric patients with asthma, and 2) to evaluate perception on self-efficacy and satisfaction toward the discharge planning model of caregivers after developing the model. The samples whom were purposively selected, were categorized in 3 phases. 1) Problem study phase included 3 groups: (1) eleven professional nurses who worked in pediatric ward 3 and attended brain storming, (2) five caregivers of asthmatic children who were interviewed, and (3) thirty-five caregivers of asthmatic children before trial. 2) The model development phase comprised eleven professional nurses who worked in this unit. 3) The trial phase, contained thirty-five caregivers of asthmatic children after trial. The research tools consisted of the questionnaires on caregivers’ perception on self-efficacy and satisfaction toward the discharge planning model. Their reliability coefficients were 0.95 and 0.85 respectively. In the trial stage, the discharge planning model was applied in a training project. Data were analyzed by descriptive statistics. The research findings were as follows. 1) Problems situations of discharge planning for pediatric patients with asthma revealed into 3 aspects including (1) structure: the hospital had the discharge planning policy without clear guidelines, performed discharge planning by own experiences, and no caregiver’s participation. (2) A process of discharge planning was performed unsystematically and the advice was mostly done on a discharge day. (3) Outcome revealed that there were no clear follow-up and evaluation. 2) The developed discharge planning model embraced systematic steps. This procedure began with discharge planning problems and needs assessing through caregivers’ collaboration, planning, implementing, and evaluating. These were integrated with the D-METHOD format and an empowerment concept along with discharge planning charts, nebulize equipment and the manuscript, and a teaching plan. 3) After the model development, caregivers’ perception on self-efficacy and satisfaction toward the discharge planning model were at the highest level.